Pemphigus Foliaceus and Pemphigus Erythematosus are the Most Common Subtypes of Pemphigus in Northern Finland - Anna-Kaisa Försti; Ossi Vuorre; Eveliina Laurila; Jari Jokelainen; Laura Huilaja; Kaisa Tasanen (Medical Journals Sweden, 2019)
Pemphigus is an autoimmune skin disease characterized by blistering and erosions of the skin and mucous membranes. Pemphigus is rare in Northern and Western Europe but its incidence is higher around the Mediterranean Sea. The most common type worldwide is pemphigus vulgaris. The aim of this study was to investigate the incidence of pemphigus subtypes in Northern Finland between 1985 and 2017. A total of 46 patients diagnosed with pemphigus at the Department of Dermatology of Oulu University Hospital were found the female/male ratio was 1.7. In contrast to many other countries it was found that in Northern Finland the superficial pemphigus subtypes were the most common: erythematosus or foliaceus (65%) followed by pemphigus vulgaris (26%). Over the past 4 decades the annual incidence of pemphigus in Finland has increased from 0.76 to 2.8 cases per million persons.